How Changes in Entrepreneurial Orientation can Explain Pivots during the Internationalization of Digital Technology-Based Born Globals - Jathol, Bilal; Favre-Bonté, Véronique (Management international / International Management / Gestiòn Internacional, 2022)
Most theories of strategic change focus on established firms. Little research examines how early-stage entrepreneurs decide to change their strategies and pivot in an international context (Kirtley & O’Mahony, 2019). To better understand how Born Globals (BG) pivot during their rapid internationalization, we study digital technology-based mobile game development BGs. We found that pivots are mostly driven by changes in individual Entrepreneurial Orientation (EO) components. Using effectuation/causation theory, this study contributes to the understanding of both pivots in born globals and the role of changes in individual EO components over time.